Preliminary Study on Tamarindus Indica Seeds Kernel as Natural Coagulant for Color Removal of Synthetic Textile Wastewater - Kristianto, Hans; Handriono, Chandra Wendy; Soetedjo, Jenny N M (2019 International Conference on Sustainable Engineering and Creative Computing (ICSECC), 2019)
This study describes preliminary study of tamarind seeds kernel powder as natural coagulant for color removal of drimarene dark red (DDR) synthetic wastewater (20 mg/L). The effect pH (2-7), dosage (1-3 g/L), and their interactions were investigated using general factorial design. The seeds powder was also characterized using Fourier Transform Infrared Spectroscopy (FTIR) to observe the possible active coagulating agent in this study. It was found that the seeds powder contained protein that could act as coagulant. Dosage, pH, and their interactions were found to be statistically significant to the removal of DDR. Highest removal of 84.60% was obtained at pH 3 and dosage 3 g/L.